Effect of shielding gas and energy input rate on the surface geometry and microstructure of a microalloyed steel surface melted with a TIG torch. Issue 4 (2nd October 2017) - Muñoz de Escalona, P.; Mridha, S.; Baker, T. N.
Abstract: Surface engineering techniques are used to enhance surface properties, such as wear, erosion and/or corrosion of materials, by developing a functionally graded metal matrix composite layer. Recently, as an economic alternative to laser processing, a tungsten inert gas torch has been used to incorporate ceramic particles into a metal surface. This produced about 1 μm depth melted and resolidified track on the surface, which during processing, required protection by from oxygen and hydrogen environment, by a shielding gas. The present study analysed the effect of three shielding gases argon, helium, and nitrogen, on the melt zone morphology, microstructure and hardness after melting a microalloyed steel surface under different energy input conditions. The aim was to determine the optimum conditions for future research related to surface engineering, incorporating ceramic particles. The results show that when protected by argon and using energy inputs <420 J/mm, an increase of 5% in the temperature between the start and finish of the melted track was recorded, but this increased to 25% when using energy inputs >420 J/mm. It was also found, that compared to nitrogen, using argon and helium, a re-solidified homogeneous and consistent cross- section developed along the melted track.